Associations Between Maternal Community Deprivation and Infant DNA Methylation of the SLC6A4 Gene - DeLano, Kelly; Folger, Alonzo T.; Ding, Lili; Ji, Hong; Yolton, Kimberly; Ammerman, Robert T.; Van Ginkel, Judith B.; Bowers, Katherine A. (Frontiers in Public Health, 2020)
Introduction Poverty is negatively associated with health and developmental outcomes. DNA methylation (DNAm) has been proposed as a mechanism that underlies the association between adversity experienced by mothers in poverty and health and developmental outcomes in their offspring. Previous studies have identified associations between individual-level measures of stress and adversity experienced by a mother during pregnancy and infant DNAm. We hypothesized that independent of individual stresses, a mother’s community-level deprivation while she is pregnant may also be associated with DNAm among the genes of her offspring that are related to stress response and/or development. Methods Pregnant mothers (N=53) completed assessments that measured stress, adversity, and mental health. To evaluate community-level deprivation, mothers’ addresses were linked to census-level socioeconomic measures including a composite index of deprivation that combines multiple community-level indicators such as income and highest level of education received. Infant buccal cells were collected at about age 4 weeks to measure DNAm of candidate genes including NR3C1, SCG5, and SLC6A4, which are associated with the stress response and or social and emotional development. Multivariable models were employed to evaluate the association between maternal community deprivation and infant DNAm of candidate genes. Results No significant associations were identified between maternal community-level deprivation and the methylation of NR3C1 or SCG5, however, maternal community-level deprivation was significantly associated with higher mean methylation across 8 CpG sites in SLC6A4. Conclusion This study identified an association between community-level measures of deprivation experienced by a mother during pregnancy and DNAm in their offspring. These findings may have implications for understanding how the community context can impact early biology and potential function in the next generation.